Community intervention to improve knowledge and practices on commonly used drugs - Kafle, KK; Karkee, SB; Shrestha, N; Prasad, RR; Bhuju, GB; Das, PL; Chataut, BD (Kathmandu University Medical Journal, 2010)
<!--[if gte mso 9]> maya 11.9999 <![endif]--><!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: World Health Organisation (WHO) estimates that about half of all medicines are inappropriately prescribed, dispensed and sold and about half of all patients fail to take their medicines properly. Objective: The overall objective of the study was improving use of medicines in the community by creating awareness among different target groups. Materials and methods: It was a pre-post comparison of intervention implemented at the community level in purposively selected Bhaktapur District of Kathmandu Valley, Nepal. The study was conducted in the private schools of the study district. Twelve schools were randomly selected. Thereafter, students from 6-9 grades were listed from the selected schools. Then 15% of the total students in each grade were randomly selected to get six students from each grade of the each school, totaling 288 students. The households of the selected students served as the sample households for the study. Thus, there were 288 households sampled for the study. The intervention and the targeted intermediary groups consisted of a. training of schools teachers b. training of journalists c. interactive discussions of trained school teachers with school children using key messages and c. communication of key messages through the local F.M. radio, newspaper/ magazine. Results: There was a significant increase in correct knowledge on action of antibiotics and excellent knowledge on the methods of administration of antibiotics of households after the intervention. Similarly, there was a significant increase in knowledge on cough as a disease and a significant decrease in the use of cough medicines after intervention. There was also a significant increase in excellent knowledge on the sources of vitamins and a significant decrease in the use of vitamin/tonics after the intervention. Conclusion: The participation of intermediary groups eg. school teachers, journalists and school children in the implementation of intervention were successful. The groups have fulfilled the commitments in implementing the plan of action. The key messages have effectively reached the households, and the knowledge and practices of the community members in drug use have improved. Key words: Community intervention; Use of common drugs; Knowledge and practice DOI: 10.3126/kumj.v8i1.3218 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 29-34